The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1037/cou0000261
|View full text |Cite
|
Sign up to set email alerts
|

Self-compassion matters: The relationships between perceived social support, self-compassion, and subjective well-being among LGB individuals in Turkey.

Abstract: Research on the well-being of lesbian, gay, and bisexual (LGB) people has predominately focused on Western (-ized) societies where individualism, and not collectivism, is emphasized. In the present study, we utilized a mediator model via Structural Equation Modeling (SEM) to examine the relationships between self-compassion (i.e., self-kindness, common humanity, and mindfulness), perceived social support (i.e., family, friends, and significant others), and subjective well-being (i.e., life satisfaction, positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 48 publications
(123 reference statements)
4
20
1
1
Order By: Relevance
“…The finding was consistent with previous findings. For example, selfcompassion mediated the relationship between perceived social support and subjective well-being in LGB individuals and the relationship between perceived social support and subjective happiness in college students (Toplu-Demirtaş et al, 2018;Wilson et al, 2020). This finding implied that as an emotionapproached coping strategy, infertile women's self-compassion may be enhanced by perceived social support, which was thought to be a source of coping assistance (Thoits, 1986).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The finding was consistent with previous findings. For example, selfcompassion mediated the relationship between perceived social support and subjective well-being in LGB individuals and the relationship between perceived social support and subjective happiness in college students (Toplu-Demirtaş et al, 2018;Wilson et al, 2020). This finding implied that as an emotionapproached coping strategy, infertile women's self-compassion may be enhanced by perceived social support, which was thought to be a source of coping assistance (Thoits, 1986).…”
Section: Discussionmentioning
confidence: 85%
“…A positive correlation between perceived social support and self-compassion was found in college students (Neely et al, 2009;Stallman et al, 2018). In addition, Toplu-Demirtaş et al (2018) found self-compassion mediated the correlation between perceived social support from family and significant others and subjective well-being in LGB individuals, explaining the 77% of the variance in subjective well-being. Similarly, Wilson et al (2020) found the association between perceived social support and subjective happiness, assessed by Subjective Happiness Scale (SHS; Lyubomirsky and Lepper, 1999), was partially accounted by self-compassion in college students.…”
Section: Introduction Perceived Social Support Self-compassion and Life Satisfaction In Infertile Womenmentioning
confidence: 81%
“…The data were collected through using a demographic questionnaire and three other scales, which were Urdu translated versions of their original scales including the Self-Compassion Scale, 8 Multidimensional Scale for Perceived Social Support, 9 and Depression Anxiety Stress Scale. 10 A demographic form consisting of age, gender, marital status, number of family members, family system, hospital sector, living area, monthly income, and educational level was also used. Consent was taken from every participant and they were given the right to withdraw from the study.…”
Section: Methodsmentioning
confidence: 99%
“…Hope and colleagues [29] in their study on University freshmen in Canada found a positive relationship between selfcompassion and autonomy which in turn affected their goal pursuits and overall subjective wellbeing. Similarly, Toplu-Demirtas et al [30] in their research on lesbian, gay and bisexual (LGB) in Turkey show how self-compassion mediate s relationship between social interaction and wellbeing. Although, it has not been empirically established and perhaps not immediately obvious how women's physical mobility and her participation in local governance bodies are directly associated with self-compassion, it is reasonable to assume that a self-compassionate woman is more aware of her personal environment (through extra-familial social connections/ties and freedom of movement) to make empowering choices for herself; in fact in Neff's original formulation [15], social connectedness and autonomy were important dimensions of self-compassion.…”
Section: Cfa Self-compassion Based Empowerment and Psychometricsmentioning
confidence: 91%